TRNA-derived small RNA 3′U-tRFValCAC promotes tumour migration and early progression in ovarian cancer. (February 2023) - Panoutsopoulou, Konstantina; Magkou, Paraskevi; Dreyer, Tobias; Dorn, Julia; Obermayr, Eva; Mahner, Sven; van Gorp, Toon; Braicu, Ioana; Magdolen, Viktor; Zeillinger, Robert; Avgeris, Margaritis; Scorilas, Andreas
Abstract: Introduction: Despite recent advances in epithelial ovarian cancer (EOC) management, the highly heterogenous histological/molecular tumour background and patients' treatment response obstructs personalised prognosis and therapeutics. Herein, we have studied the role and clinical utility of the novel subclass of tRNA-derived small RNA fragments emerging via 3′-trailer processing of pre-tRNAs (3′U-tRFs) in EOC. Methods: SK-OV-3 and OVCAR-3 cells were used for in vitro study. Following transfection, cell growth and migration were assessed by CCK8 and wound healing assays, respectively. 3′U-tRFs levels were assessed by reverse transcription quantitative PCR (RT-qPCR), following 3′-end RNA polyadenylation. A screening (OVCAD, n = 100) and institutionally independent validation (TU Munich, n = 103) cohorts were employed for survival analysis using disease progression and patients' death as clinical end-points. Bootstrap analysis was performed for internal validation, and decision curve analysis was used to evaluate clinical benefit on disease prognosis. Results: Following primary clinical assessment, target prediction and gene ontology analyses, the 3′U-tRF ValCAC (derived from pre-tRNA ValCAC ) was highlighted to regulate cell proliferation and adhesion, and to correlate with inferior patients' outcome. 3′U-tRF ValCAC transfection of SK-OV-3 and OVCAR-3 cells resulted in significantly increased cell growth and migration, in a dose-dependent manner. Elevated tumour 3′U-tRF ValCAC levels were associated with significantly higher risk for early progression and worse survival following first-line platinum-based chemotherapy, independently of patients' clinicopathological data, chemotherapy response, and residual tumour. Interestingly, 3′U-tRF ValCAC -fitted multivariate models improved risk stratification and provided superior clinical net benefit in prediction of treatment outcome compared to disease established markers. Conclusions: 3′U-tRF ValCAC promotes tumour cell growth and migration and supports modern risk stratification and prognosis in EOC. Highlights: 3′U-tRF ValCAC enhances cell growth and migration of ovarian cancer cells. Patients with elevated 3′U-tRF ValCAC are at higher risk for early progression. 3′U-tRF ValCAC is significantly associated with poor overall survival in ovarian cancer. 3′U-tRF ValCAC -fitted multivariate models improved risk stratification and prognosis.